MANAGEMENT OF LEARNING FACILITIES ICT IN BLANGPIDIE PRIMARY SCHOOLS - Said Alwi; Bahrun; Nasir Usman (International Journal of Educational Review, Law And Social Sciences (IJERLAS), 2024)
The evolution of technology in the digital era significantly impacts various aspects of life, including the field of education. The use of Information and Communication Technology (ICT) is crucial in the educational domain, particularly in facilitating learning activities in schools. ICT learning facilities play a vital role in streamlining the educational process, amidst high expectations placed on the educational sector. However, the education system faces numerous challenges that hinder the effective implementation of teaching and learning activities in schools. Among these challenges are inadequate educational support facilities, emphasizing the importance of teachers' ICT competencies. This research aims to explore the role of teachers in implementing ICT learning facility management in elementary schools within Blangpidie District, South Aceh Regency, and their use of ICT. Employing a descriptive quantitative method, this study utilizes a survey approach with a Likert scale, supplemented by data collection techniques such as interviews, observations, and questionnaires. The quantitative research involved 30 elementary school teachers from Blangpidie District, South Aceh Regency. Validity tests resulted in 20 valid statement items with validity coefficients ranging from 0.444 to 0.925, and a questionnaire reliability of 0.979. Collected data were analyzed using descriptive statistics, revealing that teachers' efforts to enhance ICT competencies scored an average of 15.14 or 80.57%, indicating a "Very Good" category. The findings also highlight the involvement of teachers' ICT competencies in various educational aspects, such as planning, implementation, evaluation/assessment of students, use of supporting applications, efforts or methods, support, motivation for enhancing ICT competencies, and several factors hindering the improvement of teachers' competencies.